CSR communication in Spanish quoted firms - Ramiro Cea Moure (European Research on Management and Business Economics (ERMBE), 2019)
Humans communicate their activities and performance in several ways (word of mouth, signs, written language, webpage, social networks, etc.). Currently, businesses use different mechanisms to communicate their Corporate Social Responsibility (CSR) activities to foster their reputation, consumer loyalty and social recognition. Meanwhile, sceptic firms use CSR communication as a mere whitewashing strategy. Using a triangulation methodology for Spanish quoted firms (IBEX-35), this paper aims to identify the main CSR communication channels. Our study concludes that CSR communication will undergo constant change due to the evolution of communication mechanisms.
Keywords: D83; M14; 650; Communication; Corporate Social Responsibility (CSR); Spanish quoted firms; Triangulation methodology